Integrating interventions for shoreline farming and fishing into dam operation [Abstract only]. - Reis, J.; Culver, T.B.; Lacombe, Guillaume; Senaratna Sellamuttu, Sonali (2013)
As dam construction dislodges rural communities in countries with rapidly growing economies, rural development experts struggle with how to help the displaced make their livelihoods in new lacustrine environments. One question is whether the dam infrastructure can directly benefit those who remain within the vicinity of the reservoir. This study investigates through reservoir simulation how dam and reservoir management may accommodate fishers and farmers in a resettlement village in Lao People's Democratic Republic. The identified needs are for vegetable farming on the banks of the reservoir and diversified habitat for fish. The interventions investigated are 1) a lower water level during the cultivation period in order to expose the shoreline gardens and 2) constructed wetlands adjacent and connected to the reservoir to enhance fisheries. The proposed measures are evaluated with respect to changes in power generation and the availability of water for extraction from the wetland ponds during the dry season.